PENGEMBANGAN RANTAI NILAI KOMODITAS KEMIRI SEBAGAI UPAYA PENGENTASAN KEMISKINAN DAN PELESTARIAN SUMBERDAYA HUTAN DI KAWASAN HUTAN GUNUNG RINJANI LOMBOK UTARA - Muhamad Siddik; Anas Zaini; . I Ketut Budastra; Muhammad Zubair (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2018)
ABSTRACT ‌This research aims at developing value chain of the candlenut (Aleurites muccanus) and formulating a program action to make the candlenut as an economic engine for conserving forest resources within the area of Rinjani Mountain, Northern Lombok. ‌Research utilized snow ball method, while data were collected through observation, in-depth interview, virtual survey, and Focus Group Discussion (FGD). Data was then analyzed using combination of quantitative and qualitative methods. Results indicate that candlenut commodity faces many problems along its marketing channels. Candlenut trees have relatively low productivity, so that they need to be replanted using local varity. Moreover, farmers mostly sold candlenut in form of raw commodity, therefore, farmers need to be trained proper de-shelling process in order to gain more added value.